2015
DOI: 10.1021/acsnano.5b06373
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Li–S Batteries Using Amine-Functionalized Carbon Nanotubes in the Cathode

Abstract: The rechargeable lithium-sulfur (Li-S) battery is an attractive platform for high-energy, low-cost electrochemical energy storage. Practical Li-S cells are limited by several fundamental issues, including the low conductivity of sulfur and its reduction compounds with Li and the dissolution of long-chain lithium polysulfides (LiPS) into the electrolyte. We report on an approach that allows high-performance sulfur-carbon cathodes to be designed based on tethering polyethylenimine (PEI) polymers bearing large nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
164
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(175 citation statements)
references
References 48 publications
3
164
0
1
Order By: Relevance
“…Obviously, the new peaks appear after cycles at around 620 and 1050 cm -1 , which are corresponding to the N-Li and C-S bonds, respectively. 28,40 Therefore, the XPS result combining with the FT-IR spectra explicitly certify the chemical bonds formed between g-C 3 N 4 and LiPSs. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 cycling also block the electron and ion channel and decrease the accessibility of active material.…”
Section: Figurementioning
confidence: 91%
“…Obviously, the new peaks appear after cycles at around 620 and 1050 cm -1 , which are corresponding to the N-Li and C-S bonds, respectively. 28,40 Therefore, the XPS result combining with the FT-IR spectra explicitly certify the chemical bonds formed between g-C 3 N 4 and LiPSs. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 cycling also block the electron and ion channel and decrease the accessibility of active material.…”
Section: Figurementioning
confidence: 91%
“…[13][14][15] Very recently it was shown that when such additives are engineered to form physical and covalent-like chemical bonds with LiPS, they are particularly effective in providing physical barriers and thermal constraints for preventing LiPS loss to the electrolyte at equilibrium. 16,17 However, detailed studies show that even in these favorable situations there is always a certain amount of LiPS that dissolves into the electrolyte during battery cycling. 16 While this inevitable LiPS loss from the cathode might be small enough at equilibrium to be ignored from the perspective of loss of active material and capacity over time, the high reactivity of LiPS with the Li anode drives cell failure by simultaneously depleting LiPS from the electrolyte, which drives additional loss, and passivation of the lithium metal surface which increases the cell overpotential during recharge, leading to additional modes of failure such as electrolyte decomposition and Li dendrite formation at the anode.…”
Section: Introductionmentioning
confidence: 99%
“…The ACNF@MnO 2 electrode without CNT suffers from poor rate capability due to slow electron and ion transport ( Figure S8). Figure S9) [42,43]. The discharge plateaus correspond to the reduction of elemental sulfur to high-order polysulfides and then to Li 2 S/Li 2 S 2 , while the charge plateaus represent the reverse process ( Figure S10) [44].…”
Section: Resultsmentioning
confidence: 99%